The Development Of Interactive E-Book Based On Multiple Intelligences Ecosystem Topic To Train Creative Thinking Skills - Hikmaturrosyidah, Nailul; Racmadiarti, Fida (FMIPA UNNES, 2022)
Education in 21st century, students have creative thinking skills according to various intelligence. Basic competencies used are to train students to analyze ecosystem topics. This shows that basic competence is not enough to explain the concept. Therefore, it is necessary to developed interactive teaching materials that can facilitate the material delivered easily understood by students, one of which is e-book. The research objective is to produce interactive e-books based on multiple intelligences ecosystem topics to train creative thinking skills that are feasible theoretically and empirically. The study used the ADDIE model. Feasibility is theoretical in the form of validity, and empirical feasibility is readability tests and student response questionnaires. This research involved 15 students of class X MIPA 8 SMAN 2 Lamongan. Data analyzed descriptive quantitative. The results showed that e-book was feasible theoretically with a percentage of 97.16% and empirically feasible with a readability level of 10th and student responses with a percentage of 98.48%. That is, the e-book is theoretically and empirically feasible to implement in learning.